(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
According to the results of our previous investigation of the key plots, within the mountain natural forests at the territory of the NNP “Synevir”the state of these primeval forests is reflected in several essential peculiarities including the presence of the rare herbaceous species but absence of the allochtonous plants and the wide spectrum of the associations.